Cyclodextrin-Based [1]Rotaxanes on Gold Nanoparticles - Zhu, Liangliang (Molecular Diversity Preservation International (MDPI), 2012)
Transformation of mechanically interlocked molecules (e.g., rotaxanes and catenanes) into nanoscale materials or devices is an important step towards their real applications. In our current work, an azobenzene-modified β-cyclodextrin (β-CD) derivative that can form a self-inclusion complex in aqueous solution was prepared. The self-included β-CD derivative was then functionalized onto a gold nanoparticle (AuNP) surface via a ligand-exchange reaction in aqueous solution, leading to the formation of AuNP-[1]rotaxane hybrids. Corresponding non-self-included β-CD derivative functionalized AuNPs were also developed in a DMF/H(2)O mixture solution for control experiments. These hybrids were fully characterized by UV-vis and circular dichroism spectroscopies, together with transmission electron microscopy (TEM). The competitive binding behavior of the hybrids with an adamantane dimer was investigated.